A Comparison of Brain Phantom Relative Permittivity with CST Simulation Library and Existing Research - Chew, Kim Mey; Norhudah, Seman; Rubita, Sudirman; Yong, Ching Yee (IOS Press, 2014)
The development of human-like brain phantom is important for data acquisition in microwave imaging. The characteristics of the phantom should be based on the real human body dielectric properties such as relative permittivity. The development of phantom includes the greymatter and whitematter regions, each with a relative permittivity of 38 and 28 respectively at 10 GHz frequency. Results were compared with the value obtained from the standard library of Computer Simulation Technology (CST) simulation application and the existing research by Fernandez and Gabriel. Our experimental results show a positive outcome, in which the proposed mixture was adequate to represent real human brain for data acquisition.